As transformações da base econômica nos municípios do Centro Norte BR (2000-2015) - Oliveira, Thiago José Arruda de (2017)
This thesis analyzed the Northern Center municipalities and the capability of transforming its economic basis applying the export-base theory of Douglass North. Bibliographic research, locational quotient (QL) specialization quotient (CE), employment multiplier (ME) and the FIRJAN indicator of municipal development were adopted as methodology in order to analyze the performance of productive activities and inclusive institutions, which are mechanisms to foster residentes to take part of the productive process. Three periods served as reference: 2000, 2007 and 2015. As a hypothesis, it was assumed that the economic basis of its municipalities has been still accumulation of capital due to primary activity. This means inexistence of conditions to foster transformation of its base and consequently maintenance of status quo. Nevertheless, some municipalities took advantage of commodity exports to Asia and were able to expand its savings, enabling the insertion of new manufacturers which have transformed its basis. Between 1500 and 1930, river navigation, could not develop linkage effects to productive activities as earnings were destinated primarily to maintain production. Improvements of transport means occurred only after the 1930s and the construction of the federal roads BR-020, BR-135, BR-153, BR-155, BR-230 and the railroad of Carajás. Such connections enabled a constant input of human and financial capital to the Nothern Center. Furthermore, additional inputs happened due to Embrapa, Incra, Sudeco, Sudene and Sudam, federal institutions which provided modifications to this space and new economic basis inserted all microrregions of the Nothern Center to trade, promoted by the cities of Brasília/DF, Goiânia/GO, Belém/PA, São Luís/MA, Fortaleza/CE, São Paulo/SP and rest of word. Between 2000 and 2015, the mesorregion Southeast Pará became the most dinamic region of the Northern Center as a result of its multitask specialization. Tocantins can be highligthed as it concentrates most of the municipalities with high performance of the IFDM in education and health and, based on the North-South railway, should diffuse innovation in the next years. Based on those results, both hypothesis could be confirmed, showing that the first one proved that most of the municipalities, due to short internal savings, maintained its economic basis. The second one underminded that that such municipalities located within áreas of intense capital flow, specially Marabá/PA, Redenção/PA, Imperatriz/MA, Araguaína/TO, Colinas/TO, Porto Nacional/TO, Gurupi/TO, Luís Eduardo Magalhães/BA, Barreiras/BA e Floriano/PI, could attract specialized production processes and therefore transform its economic basis. Concluding, it can be affirmed that municipalities with modern infrastructure and thus which offer jobs and decent health and education structure, are capable of modifying its basis on a long term.